Guidelines for the Acute Treatment of Cerebral Edema in Neurocritical Care Patients - Cook, Aaron M.; Morgan Jones, G.; Hawryluk, Gregory W. J.; Mailloux, Patrick; McLaughlin, Diane; Papangelou, Alexander; Samuel, Sophie; Tokumaru, Sheri; Venkatasubramanian, Chitra; Zacko, Christopher; Zimmermann, Lara L.; Hirsch, Karen; et al. (Neurocritical care, 2020)
Background Acute treatment of cerebral edema and elevated intracranial pressure is a common issue in patients with neurological injury. Practical recommendations regarding selection and monitoring of therapies for initial management of cerebral edema for optimal efficacy and safety are generally lacking. This guideline evaluates the role of hyperosmolar agents (mannitol, HTS), corticosteroids, and selected non-pharmacologic therapies in the acute treatment of cerebral edema. Clinicians must be able to select appropriate therapies for initial cerebral edema management based on available evidence while balancing efficacy and safety. Methods The Neurocritical Care Society recruited experts in neurocritical care, nursing, and pharmacy to create a panel in 2017. The group generated 16 clinical questions related to initial management of cerebral edema in various neurological insults using the PICO format. A research librarian executed a comprehensive literature search through July 2018. The panel screened the identified articles for inclusion related to each specific PICO question and abstracted necessary information for pertinent publications. The panel used GRADE methodology to categorize the quality of evidence as high, moderate, low, or very low based on their confidence that the findings of each publication approximate the true effect of the therapy. Results The panel generated recommendations regarding initial management of cerebral edema in neurocritical care patients with subarachnoid hemorrhage, traumatic brain injury, acute ischemic stroke, intracerebral hemorrhage, bacterial meningitis, and hepatic encephalopathy. Conclusion The available evidence suggests hyperosmolar therapy may be helpful in reducing ICP elevations or cerebral edema in patients with SAH, TBI, AIS, ICH, and HE, although neurological outcomes do not appear to be affected. Corticosteroids appear to be helpful in reducing cerebral edema in patients with bacterial meningitis, but not ICH. Differences in therapeutic response and safety may exist between HTS and mannitol. The use of these agents in these critical clinical situations merits close monitoring for adverse effects. There is a dire need for high-quality research to better inform clinicians of the best options for individualized care of patients with cerebral edema.